LAZY3 plays a pivotal role in positive root gravitropism in Lotus japonicus. (27th September 2019) - Chen, Yaping; Xu, Shaoming; Tian, Lu; Liu, Leru; Huang, Mingchao; Xu, Xinlan; Song, Guanying; Wu, Pingzhi; Sato, Shusei; Jiang, Huawu; Wu, Guojiang
Abstract : LAZY3, polarly localized to the plasma membrane in root stele cells, is involved in rootward polar auxin transport in roots and required for positive root gravitropism in Lotus japonicus . Abstract: LAZY1 family genes play important roles in both shoot and root gravitropism in plants. Here we report a Lotus japonicus mutant that displays negative gravitropic response in primary and lateral roots. Map-based cloning identified the mutant gene LAZY3 as a functional ortholog of the LAZY1 gene. Mutation of the LAZY3 gene reduced rootward polar auxin transport (PAT) in the primary root, which was also insensitive to the PAT inhibitor N -1-naphthylphthalamic acid. Moreover, immunolocalization of enhanced green fluorescent protein-tagged LAZY3 in L. japonicus exhibited polar localization of LAZY3 on the plasma membrane in root stele cells. We therefore suggest that the polar localization of LAZY3 in stele cells might be required for PAT in L. japonicus root. LAZY3 transcripts displayed asymmetric distribution at the root tip within hours of gravistimulation, while overexpression of LAZY3 under a constitutive promoter in lazy3 plants rescued the gravitropic response in roots. These data indicate that root gravitropism depends on the presence of LAZY3 but not on its asymmetric expression in root tips. Expression of other LAZY genes in a lazy3 background did not rescue the growth direction of roots, suggesting that the LAZY3 gene plays a distinct role in root gravitropism in L. japonicus .